Molecular analysis of carnivore Protoparvovirus detected in white blood cells of naturally infected cats - Andrea Balboni; Francesca Bassi; Stefano De Arcangeli; Rosanna Zobba; Carla Dedola; Alberto Alberti; Mara Battilani (BMC Veterinary Research, 2018)
Abstract Background Cats are susceptible to feline panleukopenia virus (FPV) and canine parvovirus (CPV) variants 2a, 2b and 2c. Detection of FPV and CPV variants in apparently healthy cats and their persistence in white blood cells (WBC) and other tissues when neutralising antibodies are simultaneously present, suggest that parvovirus may persist long-term in the tissues of cats post-infection without causing clinical signs. The aim of this study was to screen a population of 54 cats from Sardinia (Italy) for the presence of both FPV and CPV DNA within buffy coat samples using polymerase chain reaction (PCR). The DNA viral load, genetic diversity, phylogeny and antibody titres against parvoviruses were investigated in the positive cats. Results Carnivore protoparvovirus 1 DNA was detected in nine cats (16.7%). Viral DNA was reassembled to FPV in four cats and to CPV (CPV-2b and 2c) in four cats; one subject showed an unusually high genetic complexity with mixed infection involving FPV and CPV-2c. Antibodies against parvovirus were detected in all subjects which tested positive to DNA parvoviruses. Conclusions The identification of FPV and CPV DNA in the WBC of asymptomatic cats, despite the presence of specific antibodies against parvoviruses, and the high genetic heterogeneity detected in one sample, confirmed the relevant epidemiological role of cats in parvovirus infection.